Lipid and protein changes in chilled sea salmon (Pseudopercis semifasciata): Effect of previous rosemary extract (Rossmarinus officinalis L.) application - Tironi, Valeria Anahi (2009)
The aim of this work was to analyze the effect of rosemary extract application (200 and 500 ppm) on lipid oxidation, colour and protein modifications during the chilled storage (1.0 ± 0.7 °C) of sea salmon. Lipid oxidation and w3-22:6 fatty acid content modification were prevented by the addition of rosemary extract. Analysis of interaction between lipid oxidation products and proteins by fluorescence showed no relationship between their temporal changes in the aqueous phase and the lipid oxidation evolution since a similar behaviour was observed in both absence and presence of antioxidant. Protein extractability and SDS-PAGE revealed no differences between muscle untreated or treated with rosemary. Fluorescent compounds evolution in organic phase would be in relation with the appearance of lipid oxidation products. In addition, rosemary extract partially prevented the loss of red colour in chilled muscle. Although protein alterations could not be prevented, rosemary extract shows to be a promissory antioxidant in sea salmon muscle.